FRAUDULENT FINANCIAL REPORTING: A PENTAGON FRAUD ANALYSIS - satria tri nanda; neneng salmiah; dina mulyana (Jurnal Ilmiah Ekonomi Dan Bisnis, 2019)
Financial statements describe the company's financial condition. There are many gaps in the financial reports that enable management to commit fraudulent financial reporting. This study purpose to analyze the pentagon fraud, namely the pressure that is proxied by the financial target, the opportunity that is proxied by the effectiveness of monitoring (ineffective monitoring); Rationalization which is proxied by change in auditor; Competence which is proxied by the change of company directors; and Arrogance which is proxied by the number of CEO images that appear (number of CEO's picture), detects fraudulent financial statements measured using the Altman Z Score. The sample used in this study were 24 pharmaceutical sub-sector manufacturing companies registered on the Indonesia Stock Exchange during the period 2015 until 2017. The type of data used is secondary data obtained from annual reports and company financial statements for the 2015-2017 period. The analysis of the data used is multiple regression using the SPSS version 16. This study found that financial stability and ineffective monitoring influence fraudulent financial statements. Whereas auditor turnover, change of directors and the number of CEO photos that appear do not affect fraudulent financial statements.